Values of functional indexes in assessment of efficacy of osteoarthritis treatment with Chondrolon and Zel T in polyclinic - O Y Maiko; G G Bagirova (Научно-практическая ревматология, 2009)
Objective. To study change of knee joints functional disability in pts with predominantly I-II stage of knee osteoarthritis (OA) with clinical tests and WOMAC index for assessment of efficacy of treatment with Chondrolon and Zel T in polyclinic. Material and methods. 70 pts with I and II stage of OA according to Kellgren-Lawrence aged from 40 to 67 years were included. They were divided in 2 groups (30 pts in group I and40 pts in group II). Group I pts were treated with Chondrolon and group II pts – with Zel T. Treatment efficacy was assessed with WOMAC index, functional Lequesne index, pain on VAS at rest and at movement, knee mobility, time of walking for 30 m and walking stairs. Results. Positive changes of all parameters were revealed in both groups: significant improvement of pain on VAS, functional tests, Lequesne index, WOMAC scales was achieved. During treatment with Zel T improvement of the efficacy measures increased slower, mainly after 12 weeks of treatment (during treatment with Chondrolon – after8 weeks). Both drugs provided functional improvement assessed by WOMAC index butChondrolon was more effective. Conclusion. Chondrolon and Zel T can be used for treatment of OA at I or II stage with moderate knee joints functional disability. Course of treatment with Zel T should be continued not less than 3 months and with Chondrolon – 2 months.